Refining measurement of swallowing safety in the Dynamic Imaging Grade of Swallowing Toxicity (DIGEST) criteria: Validation of DIGEST version 2 - Hutcheson, Katherine A.; Barbon, Carly E. A.; Alvarez, Clare P.; Warneke, Carla L. (Cancer, 2022)
Background Dynamic Imaging Grade of Swallowing Toxicity (DIGEST) is a validated method to grade the severity of pharyngeal swallowing impairment as a toxicity of cancer based on the degree and patterns of penetration/aspiration and pharyngeal residue over a standardly acquired radiographic modified barium swallow (MBS) study. Since its implementation in 2016, areas for the refinement of grading mild safety impairments have been identified by clinical and research users. The objective of this study was to assess the performance and validity of refined DIGESTsafety grading criteria (per DIGEST version 2 [DIGESTv2]). Methods Refined safety criteria were developed and vetted with clinical and research users. DIGESTv2 included 2 changes to the safety criteria. All MBSs with blinded DIGEST version 1 grading were sampled from a registry database (1331 patients underwent MBS over the period of December 2005 to July 2019). New criteria were applied to derive DIGESTsafety grading version 2. Measures of criterion validity, including the MD Anderson Dysphagia Inventory [MDADI] composite score, the Modified Barium Swallow Impairment Profile (MBSImP) pharyngeal total, the MBSImP hyolaryngeal components (items 8‐11), and the Performance Status Scale for Head and Neck Cancer Patients [PSS‐HN] diet, were correlated with DIGESTsafety and overall DIGEST grades from versions 1 and 2 and were compared pairwise between reassigned grades. Results With the application of version 2 safety criteria, 112 of 1331 examinations (8.4%) and 79 of 1331 examinations (5.9%) changed in their DIGESTsafety and overall grades, respectively. The safety and overall DIGEST grades (versions 1 and 2) significantly correlated with criterion measures, including the MBSImP pharyngeal total, laryngeal MBSImP parameters of interest, MDADI, and PSS‐HN (P < .0001); correlations maintained a similar magnitude between versions 1 and 2. Forty‐six upgraded examinations (reassigned from safety grade 1 per version 1 to grade 2 per version 2) performed similarly to other safety grade 2 examinations (version 1), and this was likewise true for 66 downgraded examinations (reassigned from safety grade 1 per version 1 to grade 0 per version 2). Conclusions Refined criteria defining mild safety impairments with the DIGEST methodology changed grades in small numbers of examinations. DIGESTv2 criteria maintained criterion validity, demonstrated ordinality, and improved the performance of the method in these rare scenarios. Lay Summary Dynamic Imaging Grade of Swallowing Toxicity (DIGEST) is a method developed and validated by the investigators in 2016 to grade the severity of pharyngeal swallowing dysfunction (dysphagia) with a decision tree or flowsheet to guide the clinician's review of a standard radiographic modified barium swallow study. This work reports on the validity of updated DIGEST criteria (version 2) that incorporate 2 modifications to the decision tree. Version 2 of Dynamic Imaging Grade of Swallowing Toxicity (DIGESTv2) incorporates 2 modifications to the decision tree used by clinicians to grade mild (grade 1) safety impairments based on patterns of laryngeal penetration/aspiration on a radiographic modified barium swallow study. Key findings of this work include 1) the criterion validity of DIGESTv2 with respect to reference measures of clinician‐graded pharyngeal swallowing impairment and patient‐reported dysphagia and 2) the ordinality of DIGESTv2.